ACCESSIBILITY AND CHILD EDUCATION: THE PROCESS OF INCLUSION OF TARGET AUDIENCE OF SPECIAL EDUCATION IN MANAUS/AM - Souza Matos, Maria Almerinda de; Souza, Danilo Batista de; Oliveira, Jaima Pinheiro de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
We present in this work discussions about the process of inclusion of the target audience of Special Education in Early Childhood Education in Manaus (AM), with emphasis on the accessibility situation. For this, we present data of students included in the schools of the Municipal Education Department of Manaus and we exemplify the condition of accessibility in two schools. Thus, we defend that the school plays an important role, since it is one of the first spaces of public experience of the child. In the context of inclusion and universal design it is expected that school spaces will be constructed taking into account the possibility of their use by all students.
Keywords: Accessibility; Child education; School inclusion